The future of ethics : sustainability, social justice, and religious creativity - Jenkins, Willis (Georgetown University Press, 2013)
The Future of Ethics interprets the big questions of sustainability and social justice through the practical problems arising from humanity's increasing power over basic systems of life. What does climate change mean for our obligations to future generations? How can the sciences work with pluralist cultures in ways that will help societies learn from ecological change?. Traditional religious ethics examines texts and traditions and highlights principles and virtuous behaviors that can apply to particular issues. Willis Jenkins develops lines of practical inquiry through ""prophetic pragmatism.